Toward a New Concept of Progressive Art: Art History in the Service of Modernisation in the Late Socialist Period. An Estonian Case - Kodres, Krista (Artium Quaestiones, 2019)
The paper deals with renewal of socialist art history in the Post-Stalinist period in Soviet Union. The modernisation of art history is discussed based on the example of the Estonian Soviet Socialist Republic (Estonian SSR), where art historians were forced to accept the Soviets’ centrally constructed Marxist-Leninist aesthetic and approach to art and art history. In the art context, the idea of progressiveness began to be reconsidered. In previous discourse, progress was linked with the “realist” artistic method that sprang from a progressive social order. Now, however, art historians found new arguments for accepting different cultures of form, both historical and contemporary, and often these arguments were “discovered” in Marxism itself. As a result, from the middle of 1950’s Soviet art historians fell into two camps in interpreting Realism: the dogmatic and revisionist, and the latter was embraced in Estonia. In 1967, a work was published by the accomplished artist Ott Kangilaski and his nephew, the art historian Jaak Kangilaski: the Kunsti kukeaabits – Basic Art Primer – subtitled “Fundamental Knowledge of Art and Art History.” In its 200 pages, Jaak Kangilaski’s Primer laid out the art history of the world. Kangilaski also chimed in, publishing an article in 1965 entitled “Disputes in Marxist Aesthetics” in the leading Estonian SSR literary journal Looming (Creation). In this paper the Art Primer is under scrutiny and the deviations and shifts in Kangilaski’s approach from the existing socialist art history canon are introduced. For Kangilaski the defining element of art was not the economic base but the “Zeitgeist,” the spirit of the era, which, as he wrote, “does not mean anything mysterious or supernatural but is simply the sum of the social views that objectively existed and exist in each phase of the development of humankind.” Thus, he openly united the “hostile classes” of the social formations and laid a foundation for the rise of common art characteristics, denoted by the term “style.” As is evidenced by various passages in the text, art transforms pursuant to the “will-to-art” (Kunstwollen) characteristic of the entire human society. Thus, under conditions of a fragile discursive pluralism in Soviet Union, quite symbolic concepts and values from formalist Western art history were “smuggled in”: concepts and values that the professional reader certainly recognised, although no names of “bourgeois” authors were mentioned. Kangilaski relied on assistance in interpretation from two grand masters of the Vienna school of art history: Alois Riegl’s term Kunstwollen and the Zeitgeist concept from Max Dvořák (Zeitgeist, Geistesgeschichte). In particular, the declaration of art’s linear, teleological “self-development” can be considered to be inspiration from the two. But Kangilaski’s reading list obviously also included Principles of Art History by Heinrich Wölfflin, who was declared an exemplary formalist art historian in earlier official Soviet historiography. Thaw-era discursive cocktail in art historiography sometimes led Kangilaski to logical contradictions. In spite of it, the Primer was an attempt to modernise the Stalinist approach to art history. In the Primer, the litmus test of the engagement with change was the new narrative of 20th century art history and the illustrative material that depicted “formalist bourgeois” artworks; 150 of the 279 plates are reproductions of Modernist avant-garde works from the early 20th century on. Put into the wider context, one can claim that art history writing in the Estonian SSR was deeply engaged with the ambivalent aims of Late Socialist Soviet politics, politics that was feared and despised but that, beginning in the late 1950s, nevertheless had shown the desire to move on and change.